Utilization of ovalbumin-propylene glycol alginate complex system for superior foam: The effect of pH-driven phase behavior. (February 2023) - Zhang, Xinyue; Sun, Zizhen; Zeng, Qi; Jin, Haobo; Wang, Simin; Jin, Yongguo; Hu, Yu; Cai, Zhaoxia
Abstract: The complex system of ovalbumin (OVA) was constructed using propylene glycol alginate (PGA), and the mechanism linking pH-driven phase behavior of the complex system to foam performance was studied in this work. According to the pH-driven phase behavior of the OVA-PGA complex system determined by turbidity, three pH levels (pH 3.0: insoluble complex, pH 4.0: soluble complex and pH 7.0: co-soluble) were selected. The OVA-PGA complex system possessed better foaming properties compared with the OVA system at the same pH level. It exhibited excellent foaming ability (160.0%) and foaming stability (80.8%) at pH 3.0 and pH 4.0, respectively. At pH 3.0, the insoluble complexes enhanced the thermodynamic activity of the protein and interfacial stability to create abundant foams. The smaller OVA-PGA soluble complexes with moderate charge at pH 4.0, possessed network-like structures capable of forming thicker and moister bubble films to avoid foam instability. The FTIR confirmed the presence of electrostatic repulsion and hydrophobic interaction in the system of pH 7.0, while electrostatic attraction was predominant at pH 3.0. Besides that, the rheological and surface tension results further indicated that insoluble complexes diffused rapidly to the air/water interface at pH 3.0, and soluble complexes with lower interfacial tension presented viscoelasticity that stabilized the interface. However, the co-soluble state of the system at pH 7.0 was detrimental to the foaming properties due to competitive adsorption and unfolding of the OVA. This work provides the theoretical support for producing superior foam and regulating foam-based food systems precisely. Graphical abstract: Image 1 Highlights: Foam performance was enhanced at various pH levels by adding polysaccharides. The pH-driven phase behavior caused differences in aerated OVA-PGA complex system. Soluble complexes formed network-like interface and greatly raised foam stability. Excellent foaming ability was showed at pH 3.0 due to OVA-PGA insoluble complexes.